Land use and land cover dynamics: prospects and challenges for demography - Côrtes, Julia Corrêa (2014)
This paper is about studies on the relationships between environment and population from an integrated perspective, and changes in the use of the land cover, focusing on the contributions and challenges for demography. Demography approached this issue in the mid-1990s and its main contribution was to highlight the importance of population components in the models, which, until then, had been presented mainly from a simple perspective and as secondary components. Although Brazilian demographers dedicated to environmental issues were studying primarily urban themes, they collaborated indirectly to the field by proposing new ways of thinking about relations between population and environment. This paper is based on the Brazilian Amazon Region and shows how the population has been considered in theories about changes in the uses and cover of the land. Growth related to the expansion of the agricultural frontiers has also been treated, as well as the model of the household life cycle (fertility and household composition) in the 1990s and, more recently, a focus on the migration component. For demography, the article argues how essential it is to broaden studies on demographic elements, rather than their volume and space, and its effects. For the construction of Land Change Science, the author insists on the importance of urban dynamics in research, the adoption of a methodology and the exercise of dialogue among the various fields of study, incorporating the contribution of demography more systematically.